Potret Pendidikan Kristiani dalam Konteks Bergereja di Indonesia pada Masa Pandemi COVID-19 - Justitia Vox Dei Hattu (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2022)
Abstract: The COVID-19 pandemic has had a significant impact on the life of the church in Indonesia, including the design of Christian education organized by the church. The pandemic, in which digital technology develops rapidly and massively, urges the church to rethink the concept and purpose of Christian education to demonstrate its critical, adaptable, and creative dimensions. Based on a literature study of the various dynamics and changes that occur in the area of Christian education during the COVID-19 pandemic, this research proposes the three fundamental transformative efforts for the churches in Indonesia to design their concept and elaborate their purposes of Christian education, focusing on strengthening relationships among people, changing ways of thinking and learning (teaching), and socializing with digital media. Keyword: christian education; COVID-19 pandemic; digital technology Abstrak: Pandemi COVID-19 berdampak signifikan terhadap kehidupan bergereja di Indonesia, termasuk pelaksanaan Pendidikan Kristiani yang diselenggarakan oleh gereja. Pandemi, yang di dalamnya teknologi digital berkembang secara cepat dan masif, mendesak gereja untuk memikirkan kembali konsep dan tujuan Pendidikan Kristianinya, sehingga mampu menunjukkan daya kritis, daya adaptasi, dan daya kreatifnya. Dengan berbasis pada studi literatur tentang berbagai dinamika yang terjadi dalam ranah Pendidikan Kristiani selama masa pandemi COVID-19, penelitian ini menawarkan tiga upaya transformatif bagi gereja-gereja di Indonesia dalam mendesain konsep dan mengelaborasi tujuan Pendidikan Kristiani yang berorientasi pada penguatan relasi antar individu, perubahan cara berpikir dan cara belajar (mengajar), serta bersosialisasi dengan media digital. Kata Kunci: pendidikan kristiani; pandemi COVID-19; teknologi digital